1979
DOI: 10.1111/j.1432-1033.1979.tb13024.x
|View full text |Cite
|
Sign up to set email alerts
|

Cobra Venom Acetylcholinesterase

Abstract: Acetylcholinesterase from cobra (Naja naja oxiana) venom has been purified by affinity chromatography to an homogeneous state, as ascertained by sodium dodecylsulfate/polyacrylamide gel electrophoresis and sedimentation analysis. The specific activity of the preparation was 5000 IU/mg with acetylcholine as substrate. Unlike acetylcholinesterases from insoluble cell structures, the native molecule of the cobra venom enzyme consists of a single polypeptide chain of molecular weight 67000 ± 2000. At high enzyme c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0
3

Year Published

1982
1982
1996
1996

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 41 publications
3
17
0
3
Order By: Relevance
“…that, in addition to glycosylation heterogeneity, charge isoforms may reflect variations in free glutamic or aspartic acids, produced by post-translational deamidation of glutamines and asparagines [15]. Such a modification may also contribute to the heterogeneity of Bungarus venom ACHE, and would explain the fact that neuraminidase treatment did not produce a single electrophoretic band.…”
Section: ® ®mentioning
confidence: 99%
“…that, in addition to glycosylation heterogeneity, charge isoforms may reflect variations in free glutamic or aspartic acids, produced by post-translational deamidation of glutamines and asparagines [15]. Such a modification may also contribute to the heterogeneity of Bungarus venom ACHE, and would explain the fact that neuraminidase treatment did not produce a single electrophoretic band.…”
Section: ® ®mentioning
confidence: 99%
“…Cobra venom AcChoEase was prepared from Naja naja oxiana venom (Tashkent Integrated Zoo Plant, U.S.S.R.) by affinity chromatography as described (31 [3H]DPA was added directly from the stock solution so that the final ethanol concentration was below 5%. The sample was adjusted to 1 mM DPA with nontritiated compound.…”
mentioning
confidence: 99%
“…Acetylcholinesterase was purified by affinity chromatography as described elsewhere [4]. Ampholine carrier ampholytes were obtained from LKB Produkter AB (Bromma).…”
Section: Muteriulsmentioning
confidence: 99%
“…In the previous paper of this series it was shown that the charge differences in cobra venom acetylcholinesterase could not be attributed to different sialic acid contents in the glucosidic part of the molecule, because neuraminidase treatment did not reduce the heterogeneity of the preparation [4]. Conformational variability and multimerization were also left out since the forms appeared in the presence of high concentrations of urea [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation